East India Company at Home, 1757-1857 (University College London, 2018)
The East India Company at Home, 1757-1857 explores how empire in Asia shaped British country houses, their interiors and the lives of their residents. It includes chapters from researchers based in a wide range of settings such as archives and libraries, museums, heritage organisations, the community of family historians and universities. It moves beyond conventional academic narratives and makes an important contribution to ongoing debates around how empire impacted Britain. The volume focuses on the propertied families of the East India Company at the height of Company rule. From the Battle of Plassey in 1757 to the outbreak of the Indian Uprising in 1857, objects, people and wealth flowed to Britain from Asia. As men in Company service increasingly shifted their activities from trade to military expansion and political administration, a new population of civil servants, army officers, surveyors and surgeons journeyed to India to make their fortunes. These Company men and their families acquired wealth, tastes and identities in India, which travelled home with them to Britain. Their stories, the biographies of their Indian possessions and the narratives of the stately homes in Britain that came to house them, frame our explorations of imperial culture and its British legacies.